Implementation of National HIV Screening Recommendations in the Indian Health Service - Brigg Reilley MPH; Jessica Leston MPH; Scott Tulloch; Lisa Neel MPH; Megan Galope MBA, MSIM; Melanie Taylor MD, MPH (Journal of the International Association of Providers of AIDS Care, 2015)
Background: The Indian Health Service (IHS), a federal agency, provides direct patient care to an estimated 1.9 million American Indian/Alaska Native patients across a large and decentralized network of health facilities. The IHS sought to implement HIV screening of adults and adolescents per national recommendations. The IHS facilities received technical support such as electronic clinical reminders (ECRs) and sample HIV-testing policies. Purpose: To determine what facility-wide policy and practices were associated with high HIV screening rates. Methods: Survey of clinical directors of 61 federal health facilities on use of ECRs, testing policies/standing orders, and other factors associated with HIV screening. These results were correlated with HIV screening performance results for each facility as derived from the IHS national database. Results: A total of 51 (84%) of 61 facilities were interviewed. In univariate analysis, factors that were correlated with higher rates of HIV screening were having an HIV screening standing order (unadjusted odds ratio [UOR] 8.7, 95% confidence interval [CI] 2.0-37.3), sexually transmitted disease (STD) screening standing order (UOR 5, CI 1.1-21.7), having an HIV ECR in place for a year or longer (UOR 10.2, CI 2.8-37.5), and inclusion of both providers and nurses in offering HIV screening (UOR 4.8, CI 1.4-16.7). In multivariate analysis, ECRs (adjusted odds ratio [AOR] 9.1, 95% CI 1.8-45.1) and STD standing orders (AOR 7.4, 95% CI 1.1-51.0) remained significantly associated with higher HIV screening. Conclusion: Policy and practice interventions such as ECRs and standing order/testing policies and delegation of screening are correlated with high HIV screening, are scalable across health networks, and will be used for improving other infectious disease screening indicators in such as STD and hepatitis C.